Developing a training curriculum for researchers working with routine data: understanding professional and lay stakeholder priorities – The CENTRIC Study - Lugg-Widger, Fiona; Munnery, Kim; Townson, Julia; Robling, Mike (International Journal of Population Data Science, 2019)
Background Analysis of routine data makes an important contribution to service evaluation and research, providing cost-efficiencies, objective outcomes, burden reduction for patient and the public and is promoted by both policy and funders. Organisational, legal and ethical governance provide a framework for research but there is an onus on researchers to maintain their awareness of good practice when working with routine data. Aim To co-produce with data provider, researcher and public stakeholders a training curriculum for researchers working with routine data. Methods A curriculum for online and face-to-face training will be developed through consultations with three stakeholder groups. The first are researchers with existing interest /experience of using routine data. An online survey will be disseminated via UK research networks encompassing a range of disciplines and sectors. The non-probabilistic survey addresses current challenges, training experiences and learning preferences. Focus groups with three UK data provider organisations (SAIL, NHS Digital, National Pupil Database) will address provider’s experience of working with researchers, any training or support they either require, provide or sign-post to and opportunities to support best practice. Thirdly, a facilitated public consultation exercise using a deliberative enquiry process will be undertaken as a day’s workshop and include lay contributors identified via the HealthWise Wales cohort. Results We will present initial results from each stakeholder engagement activity and show how this has informed the draft training curriculum and our understanding of potential benefits that the training will deliver. Conclusions The public may remain largely unaware of data captured when using public services, how it may contribute to research and the protections that apply. Involving the public in the development of researcher training informs this process and enables researchers to more effectively engage with patients and participants. Training will be promoted through data provider and research networks across sectors in the UK.